Pengaruh Penerapan Green Accounting, CSR, dan Ukuran Perusaahan Terhadap Nilai Perusahaan - Christine, Sara Christine; Lu, Tika Angelina; Nasution, Siti Aisyah; Hulu, Yunus Anugerah (Fakultas Ekonomi Prodi Akuntansi, 2025)
This report provides a comprehensive analysis of the factors influencing firm value within the Indonesian pharmaceutical industry, specifically examining the roles of Green Accounting, Corporate Social Responsibility (CSR), and Firm Size in the post-COVID-19 landscape. The research problem addresses the imperative for pharmaceutical companies to operate effectively and efficiently in a highly competitive environment to enhance performance and reputation, ultimately increasing firm value for the benefit of both shareholders and the wider community. A quantitative research design was employed, utilizing secondary data extracted from the annual reports of 11 pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2022, yielding a total of 44 observations. Data analysis was conducted using Statistical Product and Service Solutions (SPSS), incorporating Multiple Linear Regression, Classical Assumption Tests, Coefficient of Determination, Partial (t-test), and Simultaneous (F-test) Hypothesis Testing. The empirical findings reveal a nuanced interplay among the variables. Green Accounting, when assessed individually, was found to have no statistically significant effect on Firm Value (measured by Price to Book Value - PBV). In contrast, both Corporate Social Responsibility and Firm Size demonstrated a statistically significant positive partial effect on Firm Value (PBV). Crucially, the collective impact of Green Accounting, Corporate Social Responsibility, and Firm Size exhibited a significant simultaneous effect on Firm Value (PBV). These results underscore the strategic importance of integrated approaches to sustainability and corporate governance in determining firm value within this dynamic industry context.